Camphor: benefits and risks of a widely used natural product - Zuccarini, Paolo; Soldani, Giulio (Acta Biologica Szegediensis, 2009)
The main aspects of the non-clinical profile of D-camphor, a natural product widely used as a common remedy for several symptoms, are reviewed. The pharmacodynamics and toxicity of this substance are analyzed, with regard to all the literature available, in order to assess a risk profile and better understand the positive and negative results connected with its use. The general conclusion is that the main risks of camphor as a medicinal product are mainly due to a somehow diffused attitude of considering it as “not a real medicine”, and to its consequent sometimes not sufficiently careful administration.